Mechanical stress evaluation by neutrons and synchrotron radiation VI : selected, peer reviewed papers from the 6th International Conference on Mechanical Stress Evaluation by Neutrons and Synchrotron Radiation (MECA SENS VI 2011), September 7-9, 2011, Hamburg, Germany - Brokmeier, H. G. (Materials science forum ;, 2014)
The exciting and comprehensive program of the MECA SENS VI conference provided a platform for current topics within the research fields of Mechanical Stress Evaluation with Neutrons and Synchrotron Radiation. The resulting contributions in this volume offer an excellent overview of all the various aspects in this field ranging from fundamental research and modelling to practical engineering applications. The 31 papers explore all aspects of the field from fundamental research and modeling to practical engineering applications. The topics include evaluating internal stresses using rotating-slit.